Trimethylsilyl (trimethylsiloxy) acetate as a novel electrolyte additive for improvement of electrochemical performance of lithium-rich Li1.2Ni0.2Mn0.6O2 cathode in lithium-ion batteries. (10th November 2018) - Zhuang, Yan; Du, Fanghui; Zhu, Lele; Cao, Haishang; Dai, Hui; Adkins, Jason; Zhou, Qun; Zheng, Junwei
Abstract: Lithium-rich layered metal oxide electrode materials suffer from severe capacity fading and poor rate performance in lithium-ion batteries. Herein, we demonstrate that trimethylsilyl (trimethylsiloxy) acetate (bis-TMSA) can be used as a novel electrolyte additive to improve the electrochemical performance of Li1.2 Ni0.2 Mn0.6 O2 cathode (LLC). The addition of 1% bis-TMSA in the electrolyte results in a large increase in the utilization efficiency of the electrode active material. Moreover, LLC in the bis-TMSA containing electrolyte can still deliver a discharge capacity of 136.97 mAh g −1 with capacity retention of 80.1% after 374 cycles at 1C, showing a superior cyclability. An enhancement in the rate capability of the material is also observed in the presence of bis-TMSA in the electrolyte. The effect of trace amount of water in the electrolyte on has been critical to the battery cycling performance. Removal of water in the electrolyte via hydrolysis of bis-TMSA leads to suppressed decomposition of electrolyte and less corrosion of electrode active material and current collector. Thinner SEI film with less F-containing species forms on the electrode surface and better contact between electrode material and current collector are responsible for the improved cyclability and rate capability for LLC in the bis-TMSA containing electrolyte. Highlights: Trace amounts of water in electrolyte can be removed by bis-TMSA additives. Cyclability and rate capability of LLC can be improved by bis-TMSA additive. The bis-TMSA additive leads to suppressed electrolyte decomposition. Corrosion of material and current collector can be reduced by bis-TMSA additive.